“Nice to Meet You in Masks”: How Virtual Avatars Enhance User Experience on Random Video Chat Platforms - Chao Gu; Xin Sun; Wei Wei; Jie Sun; Yingjie Zeng; Lie Zhang (Journal of Theoretical and Applied Electronic Commerce Research)
This study aims to understand how interaction design can enhance the user experience of random video chats using virtual avatars (RVC–VAs). We propose a framework to explain the mechanisms underlying changes in social anxiety and flow experiences. We applied analysis of variance (ANOVA), structural equation modeling (SEM), and fuzzy set qualitative comparative analysis (fsQCA) to data collected through surveys. Our findings indicate that a second-order construct, named mysterious interaction, comprising perceived interactivity, perceived vividness, and mystery, can reduce social anxiety and positively impact flow. Novelty experience enhances flow for female users but increases social anxiety for all users. Notably, social anxiety unexpectedly showed a positive effect on flow. Based on these findings, we propose interaction design strategies that could aid in the development and optimization of RVC-VA platforms, providing specific parameters to assist designers in prioritizing and planning actionable steps. This study makes a significant contribution to the advancing of online social services and addressing users’ needs for online social interaction.